Problematika Tambang Ilegal Dalam Perspektif Hukum Pidana Di Indonesia - Fadillah, Astuti Nur (LUTUR Law Journal, 2024)
The 1945 Constitution of the Republic of Indonesia states that the earth and water and the natural resources contained therein are controlled by the state and used for the greatest prosperity of the people. The state has the right to manage and control natural resources, which will be used for the prosperity of the people. However, the polemic about the rise of illegal mining carried out by irresponsible individuals, whether carried out traditionally or using heavy equipment, is very disturbing. Law enforcement is one of the steps that can be taken to handle illegal mining cases. The use of criminal legal instruments can be used in law enforcement against illegal mining cases. Mining without a permit violates the criminal provisions of Article 158 of Law Number 3 of 2020 concerning Amendments to Law Number. 4 of 2009 concerning Mineral and Coal Mining. Mining activities have a direct physical impact on the environment, such as loss of resources and environmental damage during the mining process and even after mining is carried out.